Law Function As Instrument To Build a Stability of Moral Economy in Globalization Era - Hieronymus Soerjatisnanta; M Farid Al-Rianto (Bandar Lampung University, 2015)
Globalization is a necessity which can’t be avoided by the nations of the world. There are Many benefits that appear from globalization process, but also there is negative effect which posed by economic order difference. To cope the negative effect, it need an effort to strengthen the state role which can be done by creation of law instrument. The creation of law instrument based on the Pancasila Ideology and UUDNRI1945- Constituion.Those thing as a fundamental value in constructing the real state sovereignty. The orientation of law creation focused to create the stability of nation interest and global interest. The stability focused on 4 important aspect which are justice, exellence, efficiency, and liberty as fundamental value of moral economic law. Those 4 aspect having a fundamental value which embodied in character of law that protect and succor.